2023
DOI: 10.2298/psi220412027y
|View full text |Cite
|
Sign up to set email alerts
|

Fear of COVID-19 and sleep problems in Turkish young adults: Mediating roles of happiness and problematic social networking sites use

Abstract: There is burgeoning evidence showing the negative impact of fear of COVID-19 on various mental health outcomes. Little is known about the underlying mechanism of the relationship between fear of COVID-19 and sleep problems in times of health crisis. This study aims to examine whether fear of COVID-19 was associated with sleep problems through happiness and problematic social networking sites (SNS) use. Participants included 506 young adults (67.6% females; mean age = 28.23 ? 8.73 years) drawn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 92 publications
0
1
0
Order By: Relevance
“…Furthermore, the reduction in exercise duration ( 114 ) and longer periods of sedentary behavior in young people may induce serious health burdens to society ( 115 , 116 ). Sleep duration and sleep quality closely affect psychological wellbeings and behavioral conduct, such as the ability to control inner states or responses toward thoughts, attention, emotions, or even performance ( 117 , 118 ). Our findings observed that 32% and 19% of the young population experienced psychological and behavioral problems, respectively, during the pandemic and were associated with the economic status of the country.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the reduction in exercise duration ( 114 ) and longer periods of sedentary behavior in young people may induce serious health burdens to society ( 115 , 116 ). Sleep duration and sleep quality closely affect psychological wellbeings and behavioral conduct, such as the ability to control inner states or responses toward thoughts, attention, emotions, or even performance ( 117 , 118 ). Our findings observed that 32% and 19% of the young population experienced psychological and behavioral problems, respectively, during the pandemic and were associated with the economic status of the country.…”
Section: Discussionmentioning
confidence: 99%